PRECISION AND ACCURACY OF NORMAL AND ABNORMAL CREATININE LEVELS OF JAFFE METHOD AGAINST ENZYMATIC METHODS - Fa'iqotul Azharil Jauharoh; Anik Handayati; Museyaroh; Edy Haryanto (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: The Jaffe method is still applied with semi-automated analyzers based on picric acid reaction in many laboratories, whereas the enzymatic method is more frequently used as a reference in primary laboratories and hospitals. Purpose: To evaluate the accuracy of the Jaffe method in comparison with the enzymatic method and to assess its precision in measuring normal and abnormally high serum creatinine levels under routine laboratory conditions. Method: The study employed an analytical observational manner at the East Java Province Hajj Hospital and Bakti Analysa Laboratory. Serum samples were obtained from 30 patients with normal creatinine levels and 25 pre-dialysis patients with abnormally high creatinine levels. Accuracy was evaluated by comparing the results of the Jaffe method with those obtained using the enzymatic method, while precision was assessed by repeating the measurements 10 times for each sample. Result: The inaccuracy of the Jaffe method for normal creatinine levels was 19.20%, while for abnormally high creatinine levels, it was -9.33%. The precision value (coefficient of variation) for normal creatinine levels was 5.86%, whereas for abnormally high creatinine levels, it was 1.13%. Conclusion: The Jaffe method for measuring normal creatinine levels demonstrated poor accuracy because the inaccuracy value exceeded the ±10% limit. In contrast, the measurement of abnormally high creatinine levels showed good accuracy because the inaccuracy value remained within the ±10% range. Both normal and abnormally high creatinine measurements using the Jaffe method demonstrated good precision, as the coefficient of variation values were lower than the maximum CV limit of 6%.